2009
DOI: 10.1136/bcr.06.2009.1998
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the aorta in Turner syndrome: two cases and review of 85 cases in the literature

Abstract: Patients with Turner syndrome (TS) are at risk for aortic dissection, but the clinical profile for those at risk is not well described. In addition to reporting two new cases, we performed an electronic search to identify all reported cases of aortic dissection associated with TS. In total, 85 cases of aortic dissection in TS were reported between 1961 and 2006. Dissection occurred at a young age, 30.7 (range 4–64) years, which is significantly earlier than its occurrence in the general female population (68 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 45 publications
2
69
0
4
Order By: Relevance
“…In contrast, the International Registry of Acute Aortic Dissection found that the mean age of dissection in non-TS women is 68 years [36,38].…”
Section: Aortic Dissection In Turner Syndromementioning
confidence: 99%
“…In contrast, the International Registry of Acute Aortic Dissection found that the mean age of dissection in non-TS women is 68 years [36,38].…”
Section: Aortic Dissection In Turner Syndromementioning
confidence: 99%
“…These studies should be repeated every 5e10 years, or earlier if clinically indicated by pregnancy or by known risk factors for AD such as hypertension, bicuspid aortic valve, or coarctation. 288 A recent study investigating the effect of supraphysiological doses of growth hormone to increase adult height in patients with TS, which may have direct effects on the cardiovascular system, revealed that this regimen neither seems to affect ascending or DTA diameter beyond the increase related to the larger body size nor does it disproportionately affect cardiac dimensions. 289 3.7.1.5.…”
Section: Recommenda On 64mentioning
confidence: 99%
“…While apparently all TS patients younger than 20 years have some structural congenital heart disease, about 10% of adults with TS that have died from aortic dissection have no evidence of major structural defects on autopsy. 288 Evidence for regular screening for aortic disease in women with TS is not available. A baseline cardiovascular evaluation should be obtained at the time of diagnosis and includes MRI in addition to echocardiography.…”
Section: Recommenda On 64mentioning
confidence: 99%
“…У пациенток с СШТ наиболее частой находкой является двустворчатый аортальный клапан (12-30%) [16,17]. Коарктацию аорты обнаруживают у 7-18% больных с СШТ.…”
Section: Discussionunclassified
“…Аневризма аорты развивается у данной группы пациентов в 100 раз чаще, чем в популяции [18][19][20][21]. Основными факторами риска для увеличения раз-мера аорты при СШТ являются артериальная гипер-тензия, наличие бикуспидального аортального кла-пана, коарктации аорты, и 45, Х кариотип.…”
Section: Discussionunclassified